Implementation Common Failure Reasons for an Enterprise Resource Planning and how to avoid - Wiam Yahea Alhayek (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2017)
The purpose of this article is to explain the main reasons for the failure of the ERP and how to avoid them. The reasons are divided into two types, reasons related to the company intending to implement the program, and the reasons related to the consulting company contracted for the purpose of providing support and advice to the implementing company in the implementation of the ERP program. The analytical descriptive approach was adopted. This approach refers to the attempt to reach precise and detailed knowledge of the elements of a particular phenomenon by collecting the necessary data from a group of respondents associated with the phenomenon in question. The main conclusion of this study is that the successful implementation of such programs requires a large and joint effort from all the participating parties. And need time as well as a budget to ensure that the application costs are covered.